2013
DOI: 10.1093/icvts/ivt302
|View full text |Cite
|
Sign up to set email alerts
|

Mediastinal staging in daily practice: endosonography, followed by cervical mediastinoscopy. Do we really need both?

Abstract: In patients with a high probability of mediastinal metastases, based on imaging, and negative endosonography, cervical mediastinoscopy should not be omitted, not even when the aspirate seems representative.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
16
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 16 publications
5
16
0
Order By: Relevance
“…The remaining 42 records were assessed in the full text. Of those, 14 were included as they corresponded to the search criteria ( Table 1) (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). The size of the cohorts varied from 30 to 802 patients, with a total number of 3,550 patients.…”
Section: Methodsmentioning
confidence: 99%
“…The remaining 42 records were assessed in the full text. Of those, 14 were included as they corresponded to the search criteria ( Table 1) (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). The size of the cohorts varied from 30 to 802 patients, with a total number of 3,550 patients.…”
Section: Methodsmentioning
confidence: 99%
“…Six of 32 unique studies reported transparently on subgroups of patients undergoing mediastinal staging by different staging strategies (i.e., EBUS and/or EUS with or without mediastinoscopy) within one study. 13,24,29,[31][32][33] For assessment of the rates of unforeseen N2 disease for the various different staging strategies, these studies were subdivided in subgroups according to the strategy used. Details on the subdivided studies are provided in Appendix D in the Supplementary Data.…”
Section: Description Of Studiesmentioning
confidence: 99%
“…Of these studies, 12 evaluated EBUS, [11][12][13][14][15][16][17][18][19][20][21][22] seven evaluated EUS, 13,[23][24][25][26][27][28] and 12 evaluated combined EBUS and EUS as a staging method. 13,[29][30][31][32][33][34][35][36][37] One study was a randomized controlled trial (RCT) comparing staging by EBUS followed by EUS versus EUS followed by EBUS, and one study was an observational study comparing EBUS plus EUS versus EBUS plus EUS with use of the EBUS scope. These studies were divided into four subgroups for meta-analysis.…”
Section: Description Of Studiesmentioning
confidence: 99%
“…Therefore, we would like to emphasise the need for continued outcomes-based measures of quality, individually and institutionally, reviewing the negative predictive value and diagnostic accuracy of EBUS/EUS procedures and preoperative mediastinal nodal staging in general on a regularly basis. In our own institution, we found 8.8 mediastinoscopies have to be performed to prevent one futile thoracotomy after negative endoscopic staging [9], a number which is lowered to 6.1 when patients have suspicious mediastinal lymph nodes on fluorodeoxyglucose-positron emission tomography. Specifically for cN1-patients, 10 mediastinoscopies are needed to detect one false-negative N2 on endosonography [10].…”
mentioning
confidence: 88%